Introduction - Antyo, Joseph; Akper, Godwin; Brinkman, Martien; van der Borght, Eddy; Nieder-Heitmann, Godwin (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
A genuine concern for human dignity fosters a public culture of human rights. A concern for  dignity contributes to equality, justice and respect in civil life. But how about dignity at home? The life people live privately in their intimate relationships, within their families, is mostly withheld from public debate. Though the relationships between men and women, parents and children are evidently unequal in power and vulnerability, and thereby susceptible for abuse, they are hardly subject of public evaluation. What about dignity at home? Families are thought to be places where human dignity feels ‘at home’. The image of home as a ‘safe haven’ however, is heavily disputed by the facts. Domestic violence is widespread. Home is a paradoxical environment: it is the place where new generations are nurtured and educated in human values, and where respect and love is practised. At the same time it is the place where the dignity of especially women and children is often contested and violated. There is no other place where people are living together so intimately, and so vulnerable. This hidden side of dignity was the theme of the conference “Dignity at home and in public” that the Protestant Theological University organised together with the Faculty of Theology of the Stellenbosch University, October 25- 26, 2010 at Kampen University, the Netherlands. A selection of the contributions are gathered in this volume. By engaging in intense, personal North-South and South-North dialogues around themes as the family in the Reformed tradition, vulnerability and autonomy, domestic violence, cultural shifts in the relationships between generations, and end of life decisions, the conference continued a five-year long partnership between the two theological faculties around the theme of human dignity. This volume explores from a variety of vantage points the way in which violence threatens people’s human dignity in our respective contexts of South Africa and the Netherlands. We have come to realise that violence is never just private but is public as well; violence threatens the home, but as evident in the case of South Africa, and increasingly also in the Netherlands, also impacts the society at large.